A Systematic-Thematic Analysis on The Pattern of Research with regards to Maqāsid al-Sharīʿah in Islamic Finance - Mohamad Shafiq Mohd Aswadi; Mohd Fuad Sawari; Miszairi Sitris; Ahmad Syukran Baharuddin (USIM PRESS, 2024)
VOL. 34 NO. 1 (2022)